Host-derived delta-like canonical notch ligand 1 as a novel diagnostic biomarker for bacterial sepsis: results from a combinational secondary analysis - Hildebrand, Dagmar; Decker, Sebastian; Koch, Christian; Schmitt, Felix; Ruhrmann, Sophie; Schneck, Emmanuel; Sander, Michael; Weigand, Markus A.; Brenner, Thorsten; Heeg, Klaus; Uhle, Florian (Frontiers in Cellular and Infection Microbiology, 2019)
Background: Sepsis is a life-threatening syndrome, resulting from a dysbalanced host response to infection. However, especially the early, pro-inflammatory immune response in sepsis is similar to other inflammatory conditions without infectious cause, e.g. trauma or surgery. This aspect challenges the value of current biomarkers for diagnosis, as these are often broadly induced. We earlier identified Delta-like Protein 1 (DLL1), a canonical Notch ligand, to be released from monocytes upon bacterial stimulation. Considering the importance of monocytes in the pathophysiology of sepsis, we hypothesized that this mechanism might occur also in the clinical setting and DLL1 might serve as a biomarker of life-threatening bacterial infection. Methods: We combined samples from three different studies, including subgroups of patients with sepsis (n=80), surgical patients (n=50), trauma patients (n=36), as well as healthy controls (n=50). We assessed plasma concentrations of DLL1 using ELISA. We performed Area-under-receiver-operator-curve (AUROC) analysis to evaluate the diagnostic performance of DLL1 compared to leucocytes, C-reactive protein (CRP), and procalcitonin (PCT). Results: Plasma concentrations of DLL1 were strongly elevated already at sepsis onset and maintained elevated until day 7. In contrast, neither surgical patients nor patients after severe trauma presented with elevated levels, while conventional biomarkers of inflammation (e.g. leucocytes and CRP), responded. AUROC analysis revealed a cut-off of 30ng/ml associated with the best diagnostic performance, yielding a superior accuracy of 91% for DLL1, compared to 75%, 79% and 81% for CRP, leucocytes, and PCT. Conclusion: DLL1 is a novel host-derived biomarker for the diagnosis of sepsis with a better performance compared to established ones, most likely due to its high robustness in non-infectious inflammatory responses. Trial registration POCSEP-Trial DRKS00008090 S-247/2014 MIRSI DRKS00005463 S-097/2013 SPRINT DRKS00010991 164/14